Frequency comb from 500 Hz to 2 THz by optical rectification in zinc telluride. Issue 23 (1st November 2013) - Hagmann, M.J.; Henage, T.E.; Azad, A.K.; Taylor, A.J.; Yarotski, D.A.
Abstract : Optical rectification of ultrafast laser pulses is widely used to generate THz radiation. Here, the microwave frequency comb generated by optical rectification with a ZnTe(100) crystal and a mode‐locked ultrafast laser has been measured, showing that the harmonics are at integer multiples of the pulse repetition rate of the laser (500 Hz). Strong correlations of the peak powers of the simultaneously measured THz spectrum and the measurements of the microwave frequency comb near 7.5 GHz suggest that they have a common origin.